Pengaruh Pemanfaatan Teknologi Informasi, Efektivitas Sistem Informasi Akuntansi dan Keahlian Pengguna Terhadap Kinerja Karyawan Lembaga Perkreditan Desa di Kecamatan Abang, Kabupaten Karangasem - Ni Ketut Desi Margawati; A. A. Ayu Erna Trisnadewi (Universitas Warmadewa, 2026)
This study aims to examine how the use of information advancements, the completeness of accounting information structures, and client capacity impact the performance of LKM workers in Abang District, Karangasem Regency. The subjects in this study were the Head of LPD, Treasurer, Administration, and Credit Department at each LPD in Abang Regency. The audit system in this review used a purposive assessment strategy, with the aim of obtaining 48 delegate tests spread across more than 12 LPDs in Abang District, Karangasem Regency. This audit included review procedures in various data. The data testing technique in this review was Multiple Linear Regression using the SPSS (Statistical Package for Social Sciences) 23 application structure. The conclusion of this research states that: (1) the use of information advancements significantly influences worker performance. (2) the development of accounting information systems significantly influences the implementation of the depiction. (3) Client authority significantly influences worker execution.